Status of soil properties in relationship with soil pH in Madhupur tract of Tangail district in Bangladesh (Progressive Agriculture, 2020)
The study was intended to investigate the status of soil properties and its relation to soil pH in Madhupur tract soil of Tangail district, Bangladesh. Thirty soil samples were collected during the period from June-July, 2016 covering four types of land as high land, medium high land, medium low land and low land. The interpretative data showed that the range of pH was strongly acidic to slightly acidic (5.27- 5.90), mean pH was slightly acidic (5.61). The organic matter (OM) status was medium (2.11 to 2.33 %) and mean OM was medium (2.24 %). The Nitrogen (N) status was low (0.11 to 0.13 %) and mean N status was medium (0.12 %). The range of the Phosphorus (P) status was found very low to medium (1.63 to 11.06 µg g-1 soil) and mean P status was medium (7.37 µg g-1 soil). The Potassium (K) status was low to very high (0.15 to 0.75meq/100 g soil) and mean K status was low (0.18 meq/100 g soil). The range of the Sulfur (S) status was found from low to medium (11.73 to 16.31 µg g-1 soil), mean S status was low (13.26 µg g-1 soil). The range of the Zinc (Zn) status was found from medium to high (0.96 to 2.23 µg g-1 soil), mean Zn status was optimum (1.55 µg g-1 soil). The range of the Boron (B) status was found from medium to very high (0.39 to 0.86 µg g-1 soil), mean B status was high (0.73 µg g-1 soil). The Calcium (Ca) status was medium to optimum (4.42 to 5.23meq/100 g soil), mean Ca status was optimum (4.83 meq/100 g soil). The Magnesium (Mg) status was optimum to high (1.21 to 1.75meq/100 g soil), mean Mg status was optimum (1.37 meq/100 g soil). No significant correlation of OM and other nutrients with pH.Progressive Agriculture 30 (3): 282-287, 2019